Chromosomal rearrangement involving 11q23 locus in chronic myelogenous leukemia: a rare phenomenon frequently associated with disease progression and poor prognosis - Wang, Wei (J Hematol Oncol, 2015)
BACKGROUND: Progression of chronic myelogenous leukemia (CML) is frequently accompanied by cytogenetic evolution, commonly unbalanced chromosomal changes, such as an extra copy of Philadelphia chromosome (Ph), +8, and i(17)(q10). Balanced chromosomal translocations typically found in de novo acute myeloid leukemia occur occasionally in CML, such as inv(3)/t(3;3), t(8;21), t(15;17), and inv(16). Translocations involving the 11q23, a relatively common genetic abnormality in acute leukemia, have been seldom reported in CML. In this study, we explored the prevalence and prognostic role of 11q23 in CML. METHODS: We searched our pathology archives for CML cases diagnosed in our institution from 1998 to present. Cases with 11q23 rearrangements were retrieved. The corresponding clinicopathological data were reviewed. RESULTS: A total of 2,012 cases of CML with available karyotypes were identified. Ten (0.5%) CML cases had 11q23 rearrangement in Ph-positive cells, including 4 cases of t(9;11), 2 cases of t(11;19), and 1 case each of t(2;11), t(4;11), t(6;11), and t(4;9;11). Eight cases (80%) had other concurrent chromosomal abnormalities. There were 6 men and 4 women with a median age of 50 years (range, 21–70 years) at time of initial diagnosis of CML. 11q23 rearrangement occurred after a median period of 12.5 months (range, 0–172 months): 1 patient in chronic phase, 2 in accelerated phase, and 7 in blast phase. Eight of ten patients died after a median follow-up of 16.5 months (range, 8–186 months) following the initial diagnosis of CML, and a median of 6.7 months (range, 0.8–16.6 months) after the emergence of 11q23 rearrangement. The remaining two patients had complete remission at the last follow-up, 50.2 and 6.9 months, respectively. In addition, we also identified a case with 11q23/t(11;17) in Ph-negative cells in a patient with a history of CML. MLL involvement was tested by fluorescence in situ hybridization in 10 cases, and 7 cases (70%) were positive. CONCLUSIONS: In summary, chromosomal rearrangements involving 11q23 are rare in CML, frequently occurring in blast phase, and are often associated with other cytogenetic abnormalities. These patients had a low response rate to tyrosine kinase inhibitors and a poor prognosis.